Efeito da meditação na ansiedade e na qualidade de vida em Minorias sexuais e de gênero: um ensaio clínico randomizado - Francisco, Leilane Camila Ferreira de Lima (2020)
Introduction: Sexual and gender minorities are discriminated, which contributes to social exclusion and with vulnerability to their mental health and suffering, reflecting on the development of mental disorders, such as generalized anxiety disorder and impaired quality of life. In this context, it is perceived that actions aimed at this population are necessary, such as meditation, which acts to complement the care practices. Objective: To evaluate of meditation effect in anxiety and quality of life in sexual and gender minorities. Method: This is a prospective, controlled, parallel, open, with two arms randomized clinical trial, on the breath meditation effect in anxiety and quality of life in sexual and gender minorities students from the Federal University of Alagoas (FUAL). The sample was calculated in 50 people, 25 per group. Of these, 23 individuals participated in the experimental group, who received meditation intervention for 8 weeks, being a weekly meeting of 30min, with three meditation blocks of 10min each. In addition, this group received a meditation notebook so that it could perform daily practices of 20min in their home. The control group consisted of 19 people, also accompanied for 8 weeks, but who did not suffer exposure to any intervention. The following data collection instruments were used: Identification questionnaire, the State-Trait Anxiety Inventory (STAI), The World Health Organization Quality of Life (WHOQOL-bref) questionnaire and MINI (MINI International Neuropsychiatric Interview – Version 7.0.2). Descriptive analyses used absolute and relative frequency, mean and standard deviation. The bivariate analysis used Pearson's Chi-Square Test (χ2) and Pearson correlation, t-test and ANOVA. It was considered 95% confidence level and ρ value < 0.05. This study was approved by the Research Ethics Committee (REC) of FUAL, according to the Consent-Made Authorization Opinion under the number 2.826.905, registered and approved in the ReBEC Platform (Brazilian Registry of Clinical Trials), under the registration number RBR-3bskgt. Results: It was identified that there was a decrease in the mean of the STAI-State, when comparing the pre-test (51.87±10.20) with the 4th week (42.70±12.85) and the 8th week (41.12±14.02) in the experimental group. There was a significant reduction in STAI-State from the initial phase for the 4 weeks of meditation (ρ = 0.015). The same was observed in the STAI- Trait mean in the experimental group, with a mean of 58.65 (±7.90) in the pre-test, 4th week 54.17 (±11.30) and 8th week 51.25 (±12.83). In the overall quality of life, there was an increase in its mean from pre-test until the completion of the follow-up in the experimental group, being 48.91 (±19.18) in the pre-test, 49.45 (±19.02) in the 4th week and 53.90 (±13.47) in the 8th week. The same was not verified in the control group, where the average increased in the 4th week, but then decreased in the 8th week. No statistical significance was identified in the meditation effect on quality of life. Regarding the complaints pointed out per group, there was a significant decrease in insomnia, from the 4th week (χ2=11.25; p = 0.004) for the 8th week of practice (χ2=11.53; p = 0.009). Conclusion: It is concluded that the alternative hypothesis of this research is partially true, that is, the meditation effect presented statistical significance in relation to state anxiety, but not for quality of life in sexual and gender minorities, compared to the control group. Thus, meditation is a complementary integrative practice that helps in reducing the anxiety. Being easily accessible, low cost and can be used by any person or health professional, and nursing can use it in their care practice.